Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Problem Based Learning (PBL) yang Diintegrasikan dengan Smart TV Kabinet “Merah Putih” pada Siswa Kelas IV UPT SDN 53 Gresik: Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Problem Based Learning (PBL) yang Diintegrasikan dengan Smart TV Kabinet “Merah Putih” pada Siswa Kelas IV UPT SDN 53 Gresik - Paringga Wilwan Tikta Sari; Heppy Zakiatun Nissa; Mohamad Nastain; Paringga Wilwan Tikta Sari; Heppy Zakiatun Nissa; Mohamad Nastain (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
Science learning in elementary schools frequently remains one-directional, which limits the development of conceptual understanding and learning engagement. Prior studies tend to separate pedagogical models from technology use and rarely measure learning outcomes and engagement simultaneously. This study aims to analyze the effectiveness of the Smart TV-assisted Problem-Based Learning (PBL) model on science learning outcomes and engagement of fourth-grade elementary school students. A quasi-experimental design with a pretest-posttest control group was applied to two classes (experimental group n=22; control group n=22) selected through purposive sampling. The instruments comprised a 30-item multiple-choice achievement test, a three-dimensional engagement observation sheet, and a student response questionnaire. Content validity was examined through expert judgment, empirical validity through product-moment correlation, and reliability through Cronbach's Alpha (a=0.87). Data were analyzed using the Shapiro-Wilk test, Levene test, independent sample t-test, and N-Gain. The results indicated no significant difference at the pretest stage (p=0.412), whereas a significant difference emerged at the posttest stage (t(42)=3.21; p=0.003). The experimental group posttest mean (82.6) exceeded that of the control group (74.1), with a moderate N-Gain (g=0.62) compared to a low N-Gain (g=0.38). The engagement score of the experimental group (M=3.48) also surpassed that of the control group (M=2.91). The novelty of this study lies in integrating PBL and Smart TV within a digital pedagogy framework that measures learning outcomes and engagement concurrently. These findings carry implications for strengthening technology-based science learning practices in elementary education.